Supporting Active Aging for Persons with Severe Disabilities and Their Families Across the Life Course. (December 2019) - Reynolds, Michelle C.; Palmer, Susan B.; Barton, Kelli N.
Individuals with severe disabilities and their families can engage in person-centered and family-centered planning for aging using a life course view. Viewing aging within the context of the family and disability is essential because many people with severe disabilities depend on their families for supports in daily living, social relationships, and for activities within communities. Since eligibility-based supports are often limited, parents and other family members play large roles both financially and socially in helping their family member move through the life course into active and healthy aging. Charting the LifeCourse is a framework that both people with disabilities and their families can use to achieve desired life outcomes over time. Issues that impact active and healthy aging for people with disabilities include the aging of caregivers, death of a caregiver, limited resources for supporting physical and health concerns, staying active in the community following retirement, and maintaining social emotional connections.